Wire techniques and forms in Iranian Seljuk jewelry(432-618 AH/1040-1221 AD) (Damascus University Journal of Historical Studies, 2022)
The article dealt with the subject of "Wire techniques and forms in Iranian Seljuk jewelry". The importance of this study lies in the specificity of the time period studied, as the metal artifact industry flourished in this era to a large extent, and the decorative patterns executed on it varied. This is in addition to its goal in shedding light on this The main element used not only in constructing the body of the piece of jewelry, but also in its decoration and beauty. This is despite the difficulties represented in the lack of information - quantitatively and qualitatively - available about this type of art, in addition to the difficulty of accessing clear pictures of pieces of jewelry in order to study them in an accurate study. Of the importance of the subject is that his study sheds - in an indirect way - the light on the metallurgical industries and the manufacture of jewelry pieces in Iran - during the period studied - in general. To achieve this end, it has been relied on a methodology based on two axes, the first theoretical and the second applied. After studying the methods of manufacturing wires and their fields of use, we moved to the practical side, which depends on studying samples of Iranian jewelry pieces produced during the studied period.
Keywords: Wire techniques; Iranian Seljuk